Analysis of The Presentation of Financial Statements Based on ISAK No. 35 on The Financial Statements of Non-Profit Organizations: Case Study on Non-Profit Organizations: Palm Oil Farmers Union - Rostika, Arlini; Yartono, Nungki; Digdowiseiso , Kumba (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
This study aims to analyze the presentation of financial statements at a non-profit organization in the Palm Oil Farmers Union. Financial statements at the Palm Oil Farmers Union are regulated in PSAK 45, then on April 11, 2019, DSAK IAI officially ratified ISAK 35 and became effective on January 1, 2020, after this ratification IAI issued a statement on the withdrawal of financial accounting standards (PPSAK 13) containing the revocation of PSAK No. 45. This research data uses secondary data from the financial statements of the Palm Oil Farmers Union. Data analysis techniques using documentation techniques by "recording or accessing" secondary resources (internal and external). The results of this study are expected that each non-profit entity applies ISAK 35 which provides guidelines for presenting financial statements for non-profit entities and has been authorized by IAI